THE CHALLENGES FACED BY THE TEACHERS IN PANDEMIC COVID 19 AT SMP MUHAMMADIYAH 61 MEDAN - Yayuk Hayulina Manurung; Mutia Arda (Proceeding International Seminar of Islamic Studies, 2021)
This research is aimed to investigate the challenges faced by the teachers in Pandemic COVID 19 in SMP Muhammadiyah 61 Medan. This research was conducted by applying descriptive qualitative method and having the data collection through observation and interview by online. Then the subject of this research was 5 English teachers. The data was analysed by having the step starting with data reduction, data presentation, data verification and drawing conclusion. The finding reveals that the most dominant challenges faced the teacher in online teaching and learning was the lack of the studentsknowledge in using the learning application used by the teachers. They were still not getting used yet in this strategy because their mindset in learning was still face-to-face and they were still dependent on their teachers. Another most dominant challenge was the students limitation of having smartphone and internet quota. These challenges are in need of solution so that the students can learn effectively through this pandemic.Keywords: Challenges, Teachers, Pandemic, Covid 19